2019
DOI: 10.1097/md.0000000000014093
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban for the treatment of venous thromboembolism in real life

Abstract: The clinical profile, evolution and complications of treatment with rivaroxaban in a cohort of patients presenting with venous thromboembolism (VTE) were analyzed in an observational, non-interventional and prospective study.A total of 111 patients were included in the study. Clinical data were collected from the medical history of the patients and recorded in a specific database.Mean age was 63.8 ± 17.4 years, 53.2% of patients were men, 55.9% had at least another concomitant condition, and 40.9% at least 1 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…In current research overall drug compliance with antithrombotic drugs was reported in 296 (77.1%) DVT patients, A similar study by Kang, J. M., et al, reported the overall drug compliance 93.8% with antithrombotic drugs [23].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In current research overall drug compliance with antithrombotic drugs was reported in 296 (77.1%) DVT patients, A similar study by Kang, J. M., et al, reported the overall drug compliance 93.8% with antithrombotic drugs [23].…”
Section: Discussionsupporting
confidence: 65%
“…In current research mean age of DVT patients was 43.78 ± 12.43 [23]. Another study by Demelo-Rodríguez, P., et al, also reported the hypertension in 43.2% DVT patients, DM in 11.7% DVT patients and ischemic heart disease in 7.2% DVT patients [24].…”
Section: Discussionsupporting
confidence: 64%
“…Direct oral anticoagulants (DOAC) like rivaroxaban were designed to reduce the need of frequent coagulation monitoring in patients 42 suffering from conditions like atrial fibrillation, 43 coronary heart disease 44 and VTE, 45 as well as those in need of thromboprophylaxis. 46 However, monitoring of blood coagulation is still required for a number of demographic groups taking these drugs.…”
Section: Resultsmentioning
confidence: 99%